The Niger Delta Development Commission's approach to infrastructure and socio-economic development of the Niger Delta Region of Nigeria. - Okon, Unoanwanaile Mbiakudi (My University, 2010)
Over the past 50 years, The Niger Delta Region of Nigeria has generated millions of USD from its endowed sale of crude oil. Yet still, its people live in abject poverty and lack basic infrastructure. This propelled Government’s intervention with the introduction of the Niger Delta Development Commission as a follow up to a series of failed development initiatives as a means of offering a lasting solution to the needs of the region. But like its predecessors, it has been confronted with similar difficulties of service delivery. In this research report, failure of these programmes was seen to be mainly as a result of poor strategic long term planning, weak institutional capacity, corruption, poorly planned infrastructure delivery implementation processes and project management practice. To alleviate the sufferings in the region, there is a need for a more participatory approach and entrenchment of best practice in infrastructure delivery in the region.